Analisis Kinerja Keuangan Bank Syariah dan Peran Kebijakan Ekonomi Islam pada Masa Pandemi Covid-19 - Restu Wulan Daru; Muhammad Iqbal Fasa; Suharto Suharto (Universitas Islam Lamongan, 2021)
Abstract: The covid-19 pandemic is an epidemic of dangerous diseases that have attacked the world, including Indonesia, resulting in death. Covid-19 has a significant impact on the development of the world economy. The current pandemic has resulted in all sectors of human life, without exception. The Islamic banking financial system is being affected by the pandemic. This research aims to analyze the financial performance of Islamic banks and the role of Islamic economic policies. This research uses quantitative analysis. This research type is based on using statistical procedures. The results show that the bank's financial performance is still healthy to face the risk of loss events during the Covid-19 pandemic. The average value of the ROA ratio is 0.88%, which means it is pretty healthy. While the average value of the ROE ratio is 5.35%, which means it is pretty healthy. Meanwhile, the average NPF ratio of 3.89% means healthy, and the average value of the BOPO ratio is 90.37%, which means it is very healthy. The solutions offered include distribution of exclusive cash donations based on zakat, infak, alms, and endowments, then through donations of superior venture capital for the business sector or Micro, Small, and Medium Enterprises, as well as through the development of Islamic financial technology.